The influence of active knowledge-sharing learning model with assistance of learning animation videos on student activities and outcomes in cell division material class XII SMAN 5 Barru - Hikmah, Nurul; Mustami, Muhammad Khalifah; Syahriani, Syahriani (Journal of Islam and Science, 2023)
The students' lack of enthusiasm for learning activities and the use of inappropriate learning models contribute to the low activity levels and learning outcomes. Utilizing the active knowledge sharing learning model with the assistance of learning animation videos is one approach to overcoming these issues. The purpose of this study (1) to identify and describe the implementation of learning by using the active knowledge sharing learning model assisted by animated learning videos, (2) to identify and describe student activities and learning outcomes by using active knowledge sharing assisted by animated learning videos, (3) to identify and describe the influence of the active knowledge sharing learning model assisted by animated learning videos on student activities and learning outcomes. This research is a quasi-experimental research using nonequivalent pretest posttest control group design. The sampling technique in this study used purposive sampling method. Class XII MIPA 1 as many as 22 students as the experimental class and class XII MIPA 2 as many as 22 students as the control class. The research instrument was in the form of observation sheets for learning activities and learning outcomes tests. The data analysis technique used descriptive statistics and inferential statistics. Based on the results of the analysis it is known that the use of the active knowledge sharing learning model assisted by video animation learning on cell division material for class XII MIPA SMAN 5 Barru has a significant effect on learning activities with t_hitung>t_tabel (9.923>2.018), as well as learning outcomes with t_tabel>t_(hitung) (12.15>2.018) so that H0 is rejected and H1 is accepted.